Home plants` irrigation information measuring system - Vytovtov, Heorhii; Sosnin, Kostiantyn (My University, 2023)
In today's world of using microcontrollers, digital sensors and wireless data exchange interfaces, distributed to improve the quality of technological processes, also the use of these technologies in household processes helps to automate or simplify different routine processes. The goal of the development information-measuring system is to improve the quality of the plant growing control process in households by measuring plant growth parameters.
Keywords: microcontroller; мікроконтролер; digital sensor; цифровий датчик; wireless data exchange interface; plant growing; рослинництво